Molecular Genetics of Axial Patterning, Growth and Disease in the Drosophila Eye - Singh, Amit; Kango-Singh, Madhuri (Springer New York : Imprint: Springer, 2013)
Undoubtedly, Drosophila melanogaster, fruit fly, has proven to be one of the most popular invertebrate model organisms, and the work horse for modern day biologists. Drosophila, a highly versatile model with a genetic legacy of more than a century, provides powerful genetic, cellular, biochemical and molecular biology tools to address many questions extending from basic biology to human diseases.  One of the most important questions in biology focuses on: how does a multi-cellular organism develop from a single-celled embryo? The discovery of the genes responsible for pattern formation has helped refine this question.  Drosophila eye model has been extensively used to study molecular genetic mechanisms involved in patterning and growth. Since the genetic machinery involved in the Drosophila eye is similar to humans, it has been used to model human diseases and homology to eyes in other taxa. This book will discuss molecular genetic mechanisms of pattern formation, axial patterning, growth regulation in Drosophila eye, and more.